Strategi pengembangan objek wisata permandian alam lewaja di kabupaten enrekang - Feby Anwar; Syafri Syafri; Ilham Yahya (Journal of Urban Planning Studies, 2021)
Febi Anwar, 2020, Strategy for Developing Lewaja Natural Bathing Attractions in Enrekang Regency. Supervised by Dr.Ir. Syafri, M.Si and Ilham Yahya, ST, MSP This study examines the Development Strategy of Lewaja Natural Baths in Enrekang Regency. With the aim of the factors that hinder the development of the Lewaja Natural Baths tourism object and do not forget to also determine the development strategy of the tourist area. This research method is done by using the chi-square analysis and SWOT analysis. The results of this study are the decline in tourist visitors to the Lewaja Natural Baths where the factors of tourism facilities and tourism infrastructure are an obstacle and the lack of information and promotion is due to the lack of attention of the Lewaja Natural Baths from the local government and the lack of variety of existing tourist objects plus the increasing number of objects. tourism that is similar in other areas. Even the beauty of its potential is almost neglected due to reasons of funds and a lack of investors. related to and optimizing the natural potential in the development of the Lewaja Natural Bath tourist attraction and Optimizing and repairing tourism facilities and infrastructure maintenance. Keywords: Tourism Area Development Strategy